The character and value of vernacular security: the case of South West Cameroon. Issue 2 (3rd July 2019) - Baker, Bruce; Lekunze, Manu
ABSTRACT: This article reports the findings of field research into the vernacular understanding of security in South West Cameroon. It was found that security significantly contested; it is both objective and subjective; it is communal, whilst at the same time requiring individual l responsibility of personal security; it favours certainty and stability; it draws on a multiplicity of providers, and it goes beyond traditional conceptualisations. The findings make it clear that there are wide divergences between the typical state and donor driven security reform programmes, and people's perceived security needs. The definition of security is challenged by popular understandings. In addition, though not rejecting the need for state security, it is evident that many more actors are engaged in security provision and personal safety than state actors, and that these actors need to be accounted for in reform programmes. Conclusion draw out advantages of the vernacular approach in security reform programmes.